THE RESEARCHING OF TIRRADIANCE FLAT LAYERS OF LIQUID MEDIA IN A DOUBLE-SIDED INSTALLATIONS - Knizhka, T.; Chervinsky, L. (Energy and Automation, 2016)
The analysis of the relative flat layers’ exposure to environmental exposure of bilateral technological scheme that will improve the energy efficiency of liquid media exposure.